Influence Of Financial Audit Findings, Governments Wealth, Size Of Government And Leverage On The Performance Of Regency/City Governments In Indonesia - Andri Nugraha (TRIGIN PUBLISHER, 2021)
This study aims to determine the effect of BPK audit findings, government's wealth, size of government as well as leverage on the performance of local government districts / cities in Indonesia. The analytical method used is descriptive analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Testing Hypothesis, and the coefficient of determination. This study examined the relationship between BPK audit findings with the performance of local governments, government's wealth with local government performance, size of government with local government performance, as well as leverage the performance of local governments. The population in this study are all local government districts / cities in Indonesia, the sample in this study were 47 local government districts / cities in Indonesia. The type of data in this research is secondary data. The selection of the sampling method is a purposive sampling method. And data processing using SPSS software. The results contained in this research is the BPK audit findings and leverage partially no significant effect on the performance of the district / city in Indonesia. While the government's negative wealth effect and the size of government has positive influence on the performance of the government. And other results are BPK audit findings, government's wealth, size of government as well as leverage together have a significant influence on the financial performance of the district / city in Indonesia.